Investment plan for decreasing the cow milk production cost - VALERGAKIS (Γ. ΒΑΛΕΡΓΑΚΗΣ), G.; BANOS (Γ. ΜΠΑΝΟΣ), G. (Journal of the Hellenic Veterinary Medical Society, 2017)
The aim of this study was to investigate the possibility of decreasing cow milk production cost with an investment plan, using a sample of 120 medium and large size dairy farms in Central Macedonia. Cost reduction is considered necessary either for improving the dairy farmers' income or for maintaining it in current levels as falling milk prices are expected as a result of the new Common Agricultural Policy of the European Union. Three cost reducing factors were examined: a) increasing size of the farm (number of cows), b) increasing annual milk yield per cow and c) increasing the proportion of on-farm produced feedstuff. All three factors had significant effect on reducing cow milk production cost (P<0.01). However, while cost reduction by 1% would require increasing the number of cows by 28.3% (from an average of 86.9 to 111.5 cows per herd) or the proportion of on-farm produced feedstuff by 34% (from an average of 32.1% to 43%), the required increase in annual milk yield per cow would be only 2.2% (from an average of 6,442.5 kg to 6,586.2 kg). Furthermore, the fixed capital investment, required by each plan, would be 78,184, 16,132 and 3,475 euros, respectively.